Limonoids from Azadirachta indica var. siamensis extracts and their cytotoxic and melanogenesis-inhibitory activities - Aranya Manosroi (2018)
Six new limonoids, 7-benzoyl-17-epinimbocinol (5), 3-acetyl-7- tigloylnimbidinin (8), 1-isovaleroyl-1-detigloylsalanninolide (15), 2,3-dihydro-3α-methoxynimbolide (16), deacetyl-20,21-epoxy-20,22-dihydro- 21-deoxyisonimbinolide (26), and deacetyl-20,21,22,23-tetrahydro-20,22- dihydroxy-21,23-dimethoxynimbin (27), along with 28 known limonoids, 1-4, 6, 7, 9-14, 17-25, and 28-34, and two known flavonoids, 35 and 36, have been isolated from the extracts of bark, leaves, roots, and seeds of Azadirachta indica A. Juss. var. siamensis Valeton (Siamese neem tree; Meliaceae). The structures of the new compounds were elucidated on the basis of extensive spectroscopic analysis and comparison with literature data. All of these compounds were evaluated for their cytotoxic activities against leukemia (HL60), lung (A549), stomach (AZ521), and breast (SK-BR-3) cancer cell lines. Eleven compounds, 1, 2, 4-7, 13, 16, 17, 29, and 30, exhibited potent cytotoxicities against one or more cell lines with IC < inf > 50 < /inf > values in the range of 0.1-9.3 μM. Compound 16 induced apoptotic cell death in AZ521 cells upon evaluation of the apoptosis-inducing activity by flow cytometric analysis. Western blot analysis on AZ521 cells revealed that compound 16 activated caspases-3, -8, and -9, while increasing the ratio of Bax/Bcl-2. This suggested that 16 induced apoptosis via both mitochondrial and death receptor pathways in AZ521. In addition, upon evaluation of all compounds against the melanogenesis in B16 melanoma cells induced with α-melanocyte-stimulating hormone (α-MSH), 20 limonoids, i.e., 1-3, 6, 9-11, 18, 19, 21-29, 32, and 34, and two flavonoids, 35 and 36, exhibited melanogenesis-inhibitory activities, with no, or almost no, toxicities to the cells at lower and/or higher concentrations, which were more potent than the reference arbutin, a known melanogenesis inhibitor. Western blot analysis showed that nimbin (18) reduced the protein levels of microphtalmia-associated transcription factor (MITF), tyrosinase, tyrosine-related protein 1 (TRP-1), and TRP-2 mostly in a concentration-dependent manner, indicating that 18 inhibits melanogenesis on a α-MSH-stimulated B16 melanoma cells by, at least in part, inhibiting the expression of MITF, followed by decreasing the expression of tyrosinase, TRP-1, and TRP-2. Copyright © 2014 Verlag Helvetica Chimica Acta AG, Zürich.